2022
DOI: 10.3390/agriculture12030317
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Effects of Rhizophagus intraradices and P on Root System Architecture and P Transportation in Citrus limon L.

Abstract: Both arbuscular mycorrhizal fungi (AMF) and phosphorus (P) collectively influence the root system architecture (RSA), but whether the combination of the two affects RSA, particularly lateral root formation, is unknown. In the present study, a pot experiment was conducted to evaluate the effects of an arbuscular mycorrhizal fungus (Rhizophagus intraradices) on the RSA of lemon (Citrus limon L.) seedlings under 0 (P0) and 50 mg/kg (P50) P levels. Moreover, P and carbohydrate content; acid phosphatase activity; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Further, AMF can improve plant growth, root morphology, regulate host gene expression and cellular metabolism through various signaling molecules ( Lopez-Raez et al., 2010 ; Rivero et al., 2015 ; Hill et al., 2018 ). Previous studies have shown that AMF can regulate the expression of genes associated with root development to promote plant root development, promote the expression of root transporter genes, and improve acquisition of mineral elements by plants ( Liu et al., 2022 ; Wu et al., 2022 ). In a complimentary way, plant roots can regulate the colonization of AMF by changing the synthesis of its metabolites including that of fatty acids, flavonoids and signaling molecules ( Larose et al., 2002 ; Jin et al., 2016 ; Kameoka et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, AMF can improve plant growth, root morphology, regulate host gene expression and cellular metabolism through various signaling molecules ( Lopez-Raez et al., 2010 ; Rivero et al., 2015 ; Hill et al., 2018 ). Previous studies have shown that AMF can regulate the expression of genes associated with root development to promote plant root development, promote the expression of root transporter genes, and improve acquisition of mineral elements by plants ( Liu et al., 2022 ; Wu et al., 2022 ). In a complimentary way, plant roots can regulate the colonization of AMF by changing the synthesis of its metabolites including that of fatty acids, flavonoids and signaling molecules ( Larose et al., 2002 ; Jin et al., 2016 ; Kameoka et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of the plant material, lemon ( Citrus limon L.), were provided by the Resear-ch Institute of Fruit and Tea, Hubei Academy of Agricultural Sciences. The method of Liu et al [ 44 ] was referred to regarding seed disinfection and germination, with the germination carried out in sterilized sand (121 °C, 0.1 MPa, 1 h) for 4 weeks under the conditions of 28/20 °C (day/night) and 80% relative humidity. One non-mycorrhizal seedling with two euphylla of uniform size were selected and transplanted into one pot.…”
Section: Methodsmentioning
confidence: 99%
“…These segments were cleared using 10% potassium hydroxide and stained with a 0.05% trypan blue solution [19]. The rate of mycorrhizal colonization in the lateral roots was determined following the method described by Shao et al [14], using a Leica DME binocular light microscope (Leica Microsystem Inc., Wetzlar, Germany) for examination, and calculated as the percentage of AM infected root lengths against total root length.…”
Section: Variables Measurementmentioning
confidence: 99%
“…However, the influence of AMF on root system architecture (RSA) is subject to various factors, including soil P levels and hormonal balances. Studies on trifoliate orange (Poncirus trifoliata) and tea plants (Camellia sinensis L. O. Kuntze) have revealed that AMF infection promotes RSA, with improvements in root length, volume, surface area, and lateral root formation, which are further amplified by higher P concentrations [13,14]. In addition, AMF inoculation can also affect root hair growth, including their density and length under different soil P levels, and mycorrhiza-induced changes in root hair growth were closely related to upregulated expressions of expansin and simultaneous auxin accumulation in roots [15,16].…”
Section: Introductionmentioning
confidence: 99%